Thermodynamics and Thermokinetics to Model Phase Transitions of Polymers over Extended Temperature and Pressure Ranges Under Various Hydrostatic Fluids - Boyer, Séverine A.E.; Grolier, Jean-Pierre E.; Yoshida, Hirohisa; Haudin, Jean-Marc; Chenot, Jean-Loup (IntechOpen, 2011)
None